2022
DOI: 10.3389/fcimb.2022.980917
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Cryptosporidium species and host-adapted Cryptosporidium canis subtypes in farmed minks, raccoon dogs and foxes in Shandong, China

Abstract: Cryptosporidium spp. are common parasitic pathogens causing diarrhea in humans and various animals. Fur animals are widely farmed in Shandong Province, China, but the prevalence and genetic identity of Cryptosporidium spp. in them are unclear. In this study, 1,211 fecal samples were collected from 602 minks, 310 raccoon dogs and 299 foxes on two farms in Shandong and analyzed for Cryptosporidium spp. by nested PCR and sequence analyses of the small subunit rRNA gene. The overall infection rate of Cryptosporidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Genomic differences were observed among C. canis isolates of different host origins. Results of previous genetic characterizations of C. canis isolates at the SSU rRNA, actin and gp60 loci indicated that the fox-derived isolates are genetically different from other isolates [6, 9, 11]. In the present study, results of comparative genomics analysis of C. canis isolates indicate that while a dog-derived isolate shares ~99.9 % (~4000 SNVs) of nucleotide sequence identity with a mink-derived isolate, both isolates share only 94.0 % (~360 000 SNVs) with a fox-derived isolate.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Genomic differences were observed among C. canis isolates of different host origins. Results of previous genetic characterizations of C. canis isolates at the SSU rRNA, actin and gp60 loci indicated that the fox-derived isolates are genetically different from other isolates [6, 9, 11]. In the present study, results of comparative genomics analysis of C. canis isolates indicate that while a dog-derived isolate shares ~99.9 % (~4000 SNVs) of nucleotide sequence identity with a mink-derived isolate, both isolates share only 94.0 % (~360 000 SNVs) with a fox-derived isolate.…”
Section: Discussionsupporting
confidence: 46%
“…Disordered proteins have been identified to play important biological functions in apicomplexan parasites [80,92,93]. [6,9,11]. In the present study, results of comparative genomics analysis of C. canis isolates indicate that while a dog-derived isolate shares ~99.9 % (~4000 SNVs) of nucleotide sequence identity with a mink-derived isolate, both isolates share only 94.0 % (~360 000 SNVs) with a fox-derived isolate.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Using a specific gp60 genotyping tool (Jiang et al., 2021), we managed to amplify one of the four C. canis isolates and identify it as XXi1, the first member of novel subtype family XXi. To date, nine (XXa to XXh) subtype families of C. canis have been recognised in a variety of animal hosts including dogs, foxes, minks and racoon dogs, in addition to humans (Elmahallawy et al., 2023; Jiang et al., 2021; Murnik et al., 2022; Wang et al., 2022). The fifth canine isolate was identified as the bovine genotype of C. parvum (unknown subtype family), a zoonotic genetic variant whose primary host species are cattle and humans (Guo et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular research has identified Cryptosporidium spp. in farmed fur animals (foxes and raccoon dogs) in China [ 16 , 17 , 18 ]. During molecular studies, the zoonotic Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%